An Evaluative study of Faculty Members’ Empowerment Practices at Higher Institution Level in Wah Cantt - .Sadaf Zamir Ahmed, Hina Zamir, Maliha Hammad (JCTE, 2023)
Empowerment is essential element for an institution to reform and to cope with the changing demands at both national as well as global level as it occurs due to shared decision-making of authorized bodies and stake holders. It is an obvious expectation from the authorized body of the institution to play a vital role to promote empowerment in the institution to implement and support teacher leadership. The main objective of this study was to identify the empowerment practices of male and female faculty members at higher institutions.